Perlindungan Hukum Peserta Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan dalam Pelayanan Kesehatan - Putri, Gustina Tri Lestari; Khalid, Khalid (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to analyze the form of legal protection provided to patients holding BPJS Health cards in Medan City, as well as to examine the responsibility of BPJS Health towards participants who experience suboptimal healthcare services. Issues regarding the quality of healthcare services received by BPJS participants have become an important matter as they concern the fulfillment of basic rights to health. This research employs a normative juridical method with a statutory approach, and utilizes data collection techniques in the form of literature study and interviews with related parties, with the data analysis technique used being qualitative analysis, which involves examining and interpreting data based on applicable legal provisions, as well as connecting it with interview results obtained in the field to gain a comprehensive understanding of the implementation of legal protection. Based on the research findings, it is known that legal protection for patients holding BPJS Health cards in Medan City has been implemented in accordance with applicable laws and regulations. This legal protection is divided into two forms: Preventive protection is implemented through education, information dissemination, and ease of access in submitting complaints. Meanwhile, repressive protection is provided through dispute resolution mechanisms both through non-litigation (mediation) and litigation (court) processes. In addition, the responsibility of BPJS Health Medan branch towards participants who experience disappointment, dissatisfaction, and those who do not receive their rights related to healthcare services is manifested in the form of swift and fair actions in accordance with operational standards and applicable legal provisions. The results of this study indicate that although there are several obstacles in practice, generally the implementation of legal protection for BPJS participants in Medan City has been running and provides a foundation of protection for BPJS Health participants.